Implementasi Program Pelayanan Kependudukan Via Online (PLAVON) Dalam Kepengurusan Administrasi Kependudukan di Desa - Erlina Marista Sufianti; Ahmad Riyadh (Univiversitas Dr. Djar Wattiheluw, 2024)
The aim of this research is to explain and explain the implementation of the Online Population Services Program (PLAVON) in Prasung Village, Buduran District, Sidoarjo Regency. This study uses a qualitative descriptive research method with data sources originating from interviews, observations and literature studies. The focus of this research is the implementation of the Online Population Services (PLAVON) program in Prasung Village, Buduran District, Sidoarjo Regency. Findings from the research show that the implementation of PLAVON in Prasung Village, Sidoarjo District, is still hampered by outreach efforts to the community, and only initial outreach was carried out. E PLAVON was launched in in 2021. Until now, the availability of financial resources to support the Online Population Services Program is still limited due to the lack of adequate budget allocation. This condition means that the implementation of the Online Population Services Program has not yet reached the maximum and effective level.